HAK HADHANAH KEPADA AYAH (STUDI KASUS PUTUSAN PENGADILAN AGAMA PARIGI NOMOR PERKARA 237/PDT.G/2018/PA.PRGI) - Husain Ainulfikri A. Bajuber; Dwi Ari Kurniawati; Moh Muslim (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstrakIn household relationships, the journey of household life is different, there are differences in expressing opinions about occurring in nature by husband and wife increasing conflicts, conflicts that can continue to occur can be recaptured to look better if the relationship is ended, namely by divorce. Divorce cases in the Religious Courts in Indonesia often occur, and it is the child who will become a psychic victim in the case. The purpose of this study was to study the Judge's Basics and Considerations about the Right of Hadhanah of Children for Fathers in the Case Study of the Parigi Religious Court Case Number: 237 / Pdt.G / 2018 / PA.Prgi, looking for positive legal relations and Islamic law in the Hadhanah Right for Fathers, In addition it can add insight to the community. Based on this research, the Judge's Consideration in dropping the right of hadhanah or custody to the father, due to several factors found regarding the transfer of custody, one example is the mother who lapsed. Article 105 Compilation of Islamic Law custody or hadhanah rights for children under 12 years are the rights of mothers. Suggestions from researchers, for married couples who need to divorce, must be approved in advance the maturity taken from the point of view of religion, because in Islam it is something that is hated by God. Keywords: Due, Hadhanah, Father, Decision